Habilidades para a vida como estratégia de promoção de saúde em acadêmicos de medicina - Araújo, Laís Moreira Borges (2020)
Life Skills include a group of ten psychosocial skills that enable people to deal effectively with day-to-day demands, challenges and conflicts, allowing them to act assertively, related to the environment and providing well-being. be. The World Health Organization suggests that programs be developed to reduce risky behavior and increase care for people's mental and physical health. In this sense, it is necessary to invest in training so that they can increase their power of decision on issues that affect their life. The aim of this study was to verify whether participation in a life skills intervention program reduces anxiety in medical students. It is a quasi-experimental study, with a qualitative and quantitative approach, developed in a University Center located in the interior of the state of Minas Gerais. The selection of participants was intentional, and the sample consisted of academics from the first to the sixth year of the medical course. Six groups were held, with ten places for each year, totaling sixty places. For data collection, four self-administered questionnaires were used: Sociodemographic Characterization Questionnaire, Habilidometer, Beck Anxiety Inventory and Final Evaluation Questionnaire of the Life Skills Program. For the analysis of qualitative data, content analysis was used, and for the analysis of quantitative data, a descriptive analysis was performed and the paired Student t-test was used, and the Hedges g coefficient was calculated. The participants felt stronger, with a statistically significant increase, in relation to the skills of self-knowledge, decision-making, critical thinking, creative thinking, handling feelings and emotions, handling stress and handling problems and conflicts. The mean of anxiety was significantly reduced after the intervention. The effect size for all significant results was close to 0.8, which is considered a strong effect. The significant improvement in most of the investigated medical students' life skills indicates that the intervention has achieved its objective. This is important because medical students, who in the future have become medical professionals, need to have more developed life skills for an effective completion of studies and future professional practice. Keywords: Keywords: Medical Students. Life skills. Health promotion.